Customers’ Loss of Confidence in Banking Security Systems: A Case Study of the Loss of BRI Customers’ Funds - Aisyah Safitri; Sitti Nur Aini; Moh. Ali Fajar Sidiq; Achmarul Fajar (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The phenomenon of customer funds going missing in the banking sector, particularly in the case of Bank Rakyat Indonesia (BRI), has raised concerns about the security of the digital banking system and has led to a decline in public confidence. This study aims to analyse the crisis of customer confidence in banking security systems by examining influencing factors, such as cyber risk, risk perception, and the role of social media. The research method employed is a qualitative approach using case studies, utilising secondary data obtained from academic journals, institutional reports, and case documentation.The research findings indicate that the loss of customer funds is influenced by vulnerabilities in digital security systems and the rise in cybercrime, such as phishing and social engineering. Furthermore, these incidents have led to a decline in customer trust, a trend exacerbated by the dissemination of information via social media. This study concludes that the crisis of customer trust is caused not only by technical factors, but also by risk perceptions and the dynamics of public information. Therefore, improvements in banking system security, strengthened consumer protection, and effective communication strategies are required to maintain customer trust.